Nível de qualidade em atendimento de Service Desk em Espanhol e emprego de características linguísticas: uma pesquisa baseada em corpus - Silva, Bárbara Soares da (2013)
As the world economy becomes more internationalized, domestic companies offer phone call services in different languages to their customers. This study looks at data belonging to an American company based in Brazil that was hired by a Brazilian multinational corporation to provide Service Desk support by phone to its customers. A service desk is a primary IT service called for in IT service management (ITSM) as defined by the Information Technology Infrastructure Library (ITIL) methodology. It is intended to provide a Single Point of Contact to meet communication needs of both users and IT employees. In this study, the goal is to relate quality standards and it s linguistic features in Service Desk calls held in Spanish. Research methodology includes the following steps: First, a set of calls were collected enabling a corpus of 70 texts that was fully tagged with Biber Spanish Tagger. Secondly, data research has been submitted to SPSS (statistics software) and hand annotation on quality desempenho levels and its linguistic features was done through a taxonomy developed for this research drawing on Hoey (1983). The proposed research is justified due to the fact that the study aims mainly in contributing to Corpus Linguistics filling out corporate telephone service rendering in Spanish and Portuguese language considering there is no previous research in Service Desk area and through the analysis of these languages. Results indicate incidence of calls issues that can be assessed and worked on at a level basis which can raise awareness of attendants to the linguistics characterization of service desk calls